S104 Factors affecting sensitising EGFR mutation rate and cell type in stage IIIB/IV lung cancer. (12th November 2015) - Kennedy, MPT; Quinn, JA; Biswas, AR; Rothwell, A; Scally, A; Cheyne, L; Callister, MEJ
Abstract : Introduction: Treatments for advanced lung cancer in patients with a poor performance status are limited. Such patients (PS 3–4) may not be suitable for chemotherapy for NSCLC, but may benefit from chemotherapy if SCLC is confirmed or treatment with an EGFR-TKI if an EGFR sensitising mutation (EGFR-sm) is detected. Estimates of the likelihood of detecting these two subtypes will enable patients to make informed decisions about undergoing biopsy confirmation. Aim: To analyse patient factors that affect the frequency of sensitising EGFR mutations and cell types in patients with stage IIIB/IV lung cancer. Method: Retrospective review of an electronic database of stage IIIB/IV lung cancer patients with known cell type from 2008- 2013 where a quantified smoking history was available. Where EGFR testing was not performed, the estimated prevalence of EGFR-sm was extrapolated from those patients tested according to cell type. Patients with small cell and large cell lung cancer were presumed to be EGFR wild type. Results: 1033 were identified who fulfilled the inclusion criteria. Cell types were as follows: Adenocarcinoma 31.2%, Squamous Cell 23.5%, Small Cell 22.7%, NSCLC NOS 16.2% and Large Cell 6.4%. Of 348 (33.7%) undergoing genetic testing, EGFR-sm were found in 39 (11.2%) patients. These included 32 of 241 (13.3%) adenocarcinoma, 6 of 80 (7.5%) NOS and 1 of 27 (3.7%) squamous cell. The prevalence of EGFR-sm was estimated for the 384 patients with Adenocaricinoma, NOS and Squamous Cell Carcinoma who were not tested. Table 1 shows the effect of age and pack year smoking history on EGFR mutation status and cell type. Logistic regression analysis shows increasing pack years (p < 0.001) and younger age (p = 0.004) are associated with a lower rate of sensitising EGFR mutations. Increasing pack years is associated with a higher frequency of small cell cancers, but this is not affected by age. Conclusion: Smoking status significantly impacts the likelihood of detecting both EGFR-sm and SCLC, whereas age alters the likelihood of EGFR-sm alone. These data may allow a more informed discussion regarding the likelihood of detecting an actionable result in patients with advanced lung cancer with poor performance when discussing options for biopsy.